2014
DOI: 10.4172/2155-6148.1000480
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Etomidate-Fentanyl versus Dexmedetomidine-Ketamine for Procedural Sedation and Analgesia during Upper Endoscopy and Biopsy: A Prospective, Randomized Study

Abstract: Objective: To assess the effectiveness of a combination of etomidate-fentanyl versus dexmedetomidineketamine for Procedural Sedation and Analgesia (PSA) in patients undergoing upper endoscopy and biopsy. Patients and methods: This is a prospective randomized observer-blinded study. This study was carried out in Tanta university hospital on 100 patients of both sexes; ASA physical status I and II, age range from 20-60 years undergone upper endoscopy and biopsy. All patients were randomly divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The findings of our study are consistent with the findings of many previous studies [35][36][37][38][39] that compared the effects of dexmedetomidine in combination with other drugs to assess the efficacy of sedation, hemodynamic stability, recovery criteria, and satisfaction scores for patients scheduled for GIE procedures, which revealed that the combination dexmedetomidine group outperformed the other combinations in terms of sedation efficacy and safety, hemodynamic stability, recovery criteria, analgesia, and satisfaction scores. However, other studies conducted by [40][41][42][43][44] revealed inefficacy of sedation scores and the need for higher doses of adjuvant drugs to achieve the target level of sedation with less hemodynamic stability and poor recovery criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study are consistent with the findings of many previous studies [35][36][37][38][39] that compared the effects of dexmedetomidine in combination with other drugs to assess the efficacy of sedation, hemodynamic stability, recovery criteria, and satisfaction scores for patients scheduled for GIE procedures, which revealed that the combination dexmedetomidine group outperformed the other combinations in terms of sedation efficacy and safety, hemodynamic stability, recovery criteria, analgesia, and satisfaction scores. However, other studies conducted by [40][41][42][43][44] revealed inefficacy of sedation scores and the need for higher doses of adjuvant drugs to achieve the target level of sedation with less hemodynamic stability and poor recovery criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was found that etomidate-fentanyl combination resulted in earlier onset and shorter duration of sedation, consistent with the study carried out by El-Shmaa NS and El-Baradey GF in the year 2014. [15] Possible reasons behind the above results are [16]  Short initial distribution half-life of etomidate.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalant anesthetics (isoflurane) induce unconsciousness, amnesia, muscle relaxation, blunting of autonomic reflexes and immobility. Ketamine does not produce muscular relaxation (Shmaa and Baradey, 2014).…”
Section: Mechanism Of Action Of Anesthetic Drugsmentioning
confidence: 96%